(untitled) (Contemporary Journal of Social Science Review, 2024)
This study explores the relationship between mindfulness and psychological well-being, examining the mediating roles of social connectedness and self-esteem among SMEs employees in Pakistan. A sample of 700 SMEs employees completed online questionnaires on mindfulness, social connectedness, self-esteem, and psychological well-being. Using Smart PLS for analysis, the results indicate that mindfulness is significantly related to psychological well-being. Furthermore, social connectedness and self-esteem mediate the relationship between mindfulness and psychological well-being. Specifically, mindfulness directly and indirectly influences psychological well-being through self-esteem and social connectedness. The mediating effect of self-esteem was found to be stronger than that of social connectedness. This research contributes to understanding mindfulness’s psychological mechanisms and effects on well-being, particularly within a collectivist cultural context like Pakistan, where social relationships significantly shape self-esteem and mental health. The findings provide valuable insights into enhancing the mental well-being of SMEs employees through MF practices and fostering social connections.